Pengaruh Ambidextrous Leadership dan Innovative Self Efficacy Terhadap Innovative Work Behaviour yang Dimediasi oleh Harmonious Work Passion - Lestari, Dwi Putri; Permono Nugroho, Sidiq (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2023)
The nature or behavior of a leader is a reflection for his subordinates or employees and the running of the organization or company itself. This study will discuss the role of ambidextrous leadership style which has a direct impact on workers' innovation capabilities or innovative work behavior. Ambidextrous leadership, which combines the ability to exploit existing resources and explore new opportunities, is considered a key factor in creating a work environment that supports innovation. This study uses a quantitative research type. In this study, primary data was obtained through questionnaires distributed to batik craftsmen in Solo Raya.The results of the study showed that there was a positive and significant influence between ambidextrous leadership and innovative work behavior in batik batik craftsmen in Solo Raya. In addition, innovative self-efficacy also had a significant positive effect on innovative work behavior. The role of Harmonious Work Passion as a mediator was proven to mediate the relationship between ambidextrous leadership and innovative work behavior, but did not mediate between innovative self-efficacy and innovative work behavior. This shows that harmonious work spirit can increase the influence of only one independent variable